Uso del Misoprostol en la inducción del trabajo de parto. Hospital General DR. Liborio Panchana Sotomayor. Agosto 2016–enero 2017 - Zea Morales, Alex Humberto; Lituma Peñarreta, Oscar Fernando; Avalos Moreno, Elsy Ivonne; Castro García, Raúl Germán (RECIMUNDO, 2020)